Programming in C# level 1 - Miles, Timothy J.; Safari eBooks ([S.l.] : CompuWorks, 2013)
"This course is the beginning track for certification. It is designed for the beginning C# programmer although there are topics of an advanced nature. The topics discussed within this curriculum focus primarily on C# code and not interface design or true event-based programming."--Resource description page.
Title from title screen.
Date of publication from resource description page (viewed May 29, 2013).
Presenter, Timothy J. Miles.
Keywords: C# (Computer program language); Object-oriented programming (Computer science); Electronic books